Diplomatic Agents’ Privileges and Immunities - Allan Abu Samra, Lama (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2023)
This research examines the extent of diplomatic immunity, specifically in cases where a diplomat commits a criminal offense. This situation raises concerns as it contradicts the fundamental principles upon which diplomatic relations between countries are established, namely, the promotion of economic, social, and cultural ties. The occurrence of such crimes committed by a diplomatic agent undermines the very purpose of fostering these relations. This issue necessitates an investigation into the fundamental characteristics and attributes of diplomatic immunity. It has been observed in global conventions and customary international law that states generally do not relinquish the immunity of their diplomatic representatives, unless the diplomat engages in a non-task-related criminal act, thereby permitting prosecution within the host state's jurisdiction.